Nature does it better: mimicking in vivo conditions to resolve in vitro production side effects - Dalle Palle, Enrico; Tekin, Koray; Stelletta, Calogero (Frontiers in Veterinary Science, 2025)
Oviduct represents the original place of fertilisation and early embryo development in all the domestic animals. In past time it has been considered a mere channel but new reproductive biotechnology approaches suggested the need of structurally and functionally efficient oviductal environment for in vitro embryo production. Recreating the oviductal microenvironment in IVP systems represents a paradigm shift in reproductive biotechnology. By incorporating reproductive fluids and utilising advanced 3D culture models could be reduced adverse IVP outcomes, and bring assisted reproduction closer to its natural counterpart.